Simulasi Jaringan MAN (Metropolitan Area Network) Menggunakan Metode Static Nat IPV4 Dan IPV6 - Arif Novriadi; Dodi Siregar; Mufida Khairani (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Advances in information technology to support all needs and demand for information for companies through the creation of news presentation media on the development of personal computer network technology is getting higher, the need for using internet-based information makes data security vulnerable to become an important issue, to simulate computer networks requires a software called Cisco Packet Tracer. This application is used to simulate a MAN network. To connect the MAN network requires a routing. EIGRP routing is one of the most frequently used interior routing for wide coverage. MAN network works to connect different networks from a set of LAN networks. The simulation must have security to protect the server. Network address translation (NAT) is one of the methods used as IP translation to get into different networks. Based on the results of the Static NAT IPv4 IPv6 simulation trials that have been carried out, the results of traffic security on the network are obtained so that there is no IP buildup that will hinder the communication path on the server, with a Static time delay of 0.782 sec